2011
DOI: 10.3171/2011.2.peds10434
|View full text |Cite
|
Sign up to set email alerts
|

Papillary tumor of the pineal region in a 15-month-old boy

Abstract: The papillary tumor of the pineal region (PTPR) is a distinct entity that is particularly rare in the pediatric population. The authors document the youngest reported patient with this clinicopathological entity to date. A case of PTPR in a 15-month-old boy is described. Initially thought to be a tectal glioma, the tumor was later identified as a pineal region tumor after demonstrating growth on routine imaging. Diagnosis of PTPR was established by histopathological evaluation of biopsy samples, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…[5,11]. Among these patients, 10 were children under 16 years of age (Table 1) [5][6][7]12,13]. Clinical manifestations include headache, diplopia, dizziness and vomiting [5,[12][13][14].…”
Section: Histological Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…[5,11]. Among these patients, 10 were children under 16 years of age (Table 1) [5][6][7]12,13]. Clinical manifestations include headache, diplopia, dizziness and vomiting [5,[12][13][14].…”
Section: Histological Diagnosismentioning
confidence: 99%
“…A key feature of PTPR is their high risk for local recurrence. Four out of 6 pediatric patients suffered from local tumor recurrence, the others were lost to follow-up [6,12,13]. Poulgrin et al investigated the 5-year and 10-year progression free survival of all reported cases to date, which has been estimated at 34.5% and 8.6%, respectively [5].…”
Section: Histological Diagnosismentioning
confidence: 99%
“…The age distribution of PTPR patients was remarkable. The youngest patient was an infant (a 15 -month -old boy), while the oldest patient was 70 years old (1,8). Three patients were younger than ten years (1.25, 3, and 4 years).…”
Section: Discussionmentioning
confidence: 99%
“…Proton RT produced complete tumor responses in a four -year -old child (1). Another RT technique is brachytherapy.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation